125 Possibility of Shifting Domestic Supply Curve for Lamb and Goat Meat: The Case of Market Price Information in the Southeast USA. (28th November 2020) - Karki, Lila B; Karki, Uma; Mentreddy, Srinivasa R
Abstract: The United States imported 1.01 billion in lamb and goat meat in 2018, which was 5.94% higher than in 2017. However, local sheep and goat farmers are facing challenges for getting fair prices for their animals. The objective of this study was to evaluate the market price of lamb and goat meat in the Southeast United States. The surveys were introduced to 15 cities of Georgia, Alabama, Florida, Mississippi, and Tennessee. The price for lamb and goat meat was collected for three years (2017–2019). Of the 360 price observations (n = 360) collected from these cities, 290 were for lamb and 70 for goat meat. The price consisted of 27 and 12 different types of lamb and goat meat, respectively, from the selected retail and ethnic stores. Data were analyzed for descriptive statistics. The mean price for lamb ranged from 50.58/kg for rack lamb to 10.98/kg for stew bone. Similarly, the most expensive goat meat type was leg stew (26.38/kg), followed by the whole goat leg (24.18/kg), and the regular meat was the least expensive (10.32/kg). The mean price of lamb and goat meat varied as per the type of meat in each state and city. The majority of stores predominantly sold imported lamb and goat meat from Australia, New Zealand, Chile, Mexico, China, and Uruguay. The study revealed that the different types of lamb and goat meatare selling for good prices, thereby indicating a promising market for the domestic lamb and goat meat in the Southeast.